Prevalence of associated medical-related risk factors among the patients with chronic liver disease attending the Gastroenterology clinic, Teaching Hospital, Jaffna - Sujeevan, A.; Epsiba, L.; Jegapragash, V.; Anuradha, A. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
chronic progressive liver disease. In Sri Lanka previous study represents that Diabetic mellitus, Hypertension, Hyperlipidemia, and Hypothyroidism are the significant associated medical risk factors, identifying these associated risk factors significantly helps in the prevention and effective management of CLD. Objectives: To assess the prevalence of the associated medical-related factors associated with chronic liver disease among patients of the gastroenterology clinic at Teaching Hospital Jaffna. Methodology: A descriptive cross-sectional study was conducted among chronic liver disease patients attending the gastroenterology clinic at the Teaching Hospital Jaffna. A total of 99 patients who consented to participate were enrolled. Ethical approval was obtained from the Ethics Review Committee of the Faculty of Medicine, University of Jaffna. Data were collected using a structured questionnaire, and variables such as Diabetic mellitus, Hypertension, Hyperlipidemia, Hypothyroidism, and methotrexate use were analyzed by univariate analysis using SPSS 27. Results: The mean age of the participants was 49.86 years (range 12-78), and the majority (52.5%) of them were male. According to this study, for Non-Alcoholic Fatty Liver Disease (NAFLD), diabetes mellitus was highly prevalent (45.5%). Hypertension & hyperlipidemia were both found in 31.3% of participants. Methotrexate use was reported in 14.1% of participants, 15.2% of participants had hypothyroidism, and Rheumatoid Arthritis was seen in 12.1% of participants. Only 2% reported a family history of liver disease. Conclusions: Several medical-related risk factors are associated with CLD among participants attending the gastroenterology clinic in Jaffna; among them, diabetic mellitus, hypertension, hyperlipidemia, and hypothyroidism are the significant contributors to CLD. To improve the outcome of the patients, early diagnosis through the liver function test and risk-based management protocols should be implemented.
Keywords: Chronic Liver Disease; Medical-related risk factor; Non-Alcoholic Fatty Liver Disease; Teaching Hospital Jaffna